Implications of climate variability and future trends on wheat production and crop technology adaptations in southern regions of Portugal - Carvalho, Mário (2015)
The effects of climate conditions and its variability are analysed in the context of rainfed agriculture under Mediterranean climate in the south of Portugal. The reference crop is wheat using data from field experiments carried out for several years, using different amounts of nitrogen and two wheat genotypes. Wheat yields can be limited either by drought and excess of water and winter rainfall has a large effect on nitrogen response of the crop. There is a negative impact of high temperatures during April and May, but its effect depends on the wheat genotype. Supplementary irrigation, improving soil saturated hydraulic conductivity, soil bearing capacity and plant breeding for shorter grain filling period and genetic tolerance to high temperatures will be important adaptations, having in mind the present and climate change scenarios.